PENERAPAN METODE SWEEP PADA MASALAH PERMAINAN DINAMIS LINEAR KUADRATIK SISTEM DESKRIPTOR - Muhammad Wakhid Musthofa (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2014)
This paper describes the applications of sweep method in constructing a Riccati differential equation arising in the linear quadratic differential game for descriptor systems. This equation is needed in order to find the saddle-point equilibria that be a solution for the game. To find the saddle-point equilibria the game is transformed into a reduced nonsingular game. Within a transformed game the method is applied to construct the desired Riccati equation.